A fuzzy based secure QoS routing protocol using ant colony optimization for mobile Ad hoc network - Pushpa Lakshmi, R.; Vincent Antony Kumar, A. (Journal of intelligent & fuzzy systems, 2014)
Ensuring secure communication in mobile ad hoc network (MANET) is the main challenging task due to the network characteristics. In this paper, we apply fuzzy logic method and method of ant colony optimization (ACO) to establish a secure routing path with minimum delay for mobile ad hoc network. The ACO algorithm is used to establish a virtual backbone connecting cluster heads (CHs). The general ACO algorithm is modified to allow selection of routing path, based on trust value of the nodes lying in the routing path and delaying experienced in the path. The procedure uses a fuzzy logic controller to evaluate the trust value of the nodes based on node's QoS parameters: energy drain rate, lifetime of the node, packet drop rate and packet forwarding status of the node. The behavior of the protocol under various attacks is analyzed. Experimentation shows that the algorithm results in secure shortest routing path for data communication. Additionally, the packet drop rate and routing delay of the proposed routing protocol in presence of malicious nodes is fewer compared to secure cluster based routing protocol (SCBRP) and Fuzzy Logic based Security Level routing protocol (FLSL).